Avaliação da atividade biológica do extrato seco da Remiria maritima Aubl. - Oliveira, Isamar Dantas (2010)
Remiria maritime Aubl., popularly known as "capim da praia" is used as teas to treat diarrhea, kidney disease, high fever and analgesic and antiinflammatory. There are no records in the literature about its biological properties. Therefore, this study was designed to evaluate the possible action of the antimicrobial effects, antioxidant, antinociceptive and antiinflammatory effect of aqueous extract of dried sea Remiria Aubl. (ERMA) using tests in vivo and in vitro. The extract was first subjected to tests phytochemicals. Antimicrobial activity was evaluated in vitro by the technique of disk diffusion method and minimum inhibitory concentration. The antioxidant effect was observed in vitro by testing the extent of lipid peroxidation (TBARS), nitric oxide (NO) and hydroxyl radical scavenger capacity where ERMA concentrations used were 10 μg/mL, 100 μg/mL e 1 mg/mL. The antinociceptive activity was evaluated by testing the writhing induced by acetic acid 0.9% and 1% formalin. The test of motor coordination was used to assess possible effects of muscle relaxants and sedatives ERMA might interfere with the antinociceptive effects. The anti-inflammatory activity was evaluated by testing peritonitis induced by carrageenan 1%. The animals (n = 6/group) were treated 30 min before each experiment, vehicle (saline + 0.2% Tween 80, ip) or ERMA (100, 200 and 400 mg / kg, ip). The phytochemical screening showed the presence of several chemical classes: phenols, tannins, alkaloids, volatile coumarins, flavonoids, saponins and triterpenes. The ERMA demonstrated antimicrobial activity against Gram-positive and negative. Additionally, evaluation of antioxidant activity in the TBARS assay, there was a reduction of lipid peroxidation (p <0.001). In the test of NO reduction occurred in the formation of nitric oxide (p <0.001). In the test to assess the ability of hydroxyl radical scavenger was significant with (p <0.001). Treatment with ERMA intraperitoneally produced a significant decrease in the number of writhing 100 (26.0 ± 2.1, p <0.01), 200 (25.1 ± 2.4, p <0.01) and 400 mg / kg (19.3 ± 2.9, p <0.001). In the formalin test, there was a reduced response Algic significantly only in the second phase, 200 mg / kg (22.9 ± 2.9, p <0.05) and 400 mg / kg (15.3 ± 3, 9, p <0.001). In the hot plate there was no significant difference in nociceptive behavior. In Rota rod test was verified that the ERMA does not alter the motor coordination of animals. In the test of peritonitis, treatment with ERMA promoted a significant reduction in leukocyte migration induced by carrageenan at all doses 100 (8.9 ± 0.1, p <0.01), 200 (6.6 ± 0.2 p <0.01) and 400 mg / kg (3.9 ± 0.6, p <0.01) . The results suggest that ERMA has antimicrobial activity, antioxidant, antinociceptive and antiinflammatory. However, further studies are required to better assess and characterize the mechanisms involved in these effects.